Copper-catalyzed enantioselective conjugate reduction of α,β-unsaturated esters with chiral phenol–carbene ligands - Mimura, Shohei; Mizushima, Sho; Shimizu, Yohei; Sawamura, Masaya (Beilstein Journal of Organic Chemistry, 2020)
A chiral phenol–NHC ligand enabled the copper-catalyzed enantioselective conjugate reduction of α,β-unsaturated esters. The phenol moiety of the chiral NHC ligand played a critical role in producing the enantiomerically enriched products. The catalyst worked well for various (Z)-isomer substrates. Opposite enantiomers were obtained from (Z)- and (E)-isomers, with a higher enantiomeric excess from the (Z)-isomer.
Keywords: catalyst; chiral NHC; conjugate reduction; copper catalysis; enantioselective reaction

(untitled) - Mahoney, W. S.; Brestensky, D. M.; Stryker, J. M. (J. Am. Chem. Soc., 1988)

(untitled) - Mahoney, W. S.; Stryker, J. M. (J. Am. Chem. Soc., 1989)

(untitled) - Deutsch, C.; Krause, N.; Lipshutz, B. H. (Chem. Rev., 2008)

(untitled) - Appella, D. H.; Moritani, Y.; Shintani, R.; Ferreira, E. M.; Buchwald, S. L. (J. Am. Chem. Soc., 1999)

(untitled) - Moritani, Y.; Appella, D. H.; Jurkauskas, V.; Buchwald, S. L. (J. Am. Chem. Soc., 2000)

(untitled) - Lipshutz, B. H.; Servesko, J. M. (Angew. Chem., Int. Ed., 2003)

(untitled) - Hughes, G.; Kimura, M.; Buchwald, S. L. (J. Am. Chem. Soc., 2003)

(untitled) - Lipshutz, B. H.; Servesko, J. M.; Taft, B. R. (J. Am. Chem. Soc., 2004)

(untitled) - Huang, S.; Voigtritter, K. R.; Unger, J. B.; Lipshutz, B. H. (Synlett, 2010)

(untitled) - Wu, Y.; Qi, S.-B.; Wu, F.-F.; Zhang, X.-C.; Li, M.; Wu, J.; Chan, A. S. C. (Org. Lett., 2011)

(untitled) - Hou, C.-J.; Guo, W.-L.; Hu, X.-P.; Deng, J.; Zheng, Z. (Tetrahedron: Asymmetry, 2011)

(untitled) - Janssen-Müller, D.; Schlepphorst, C.; Glorius, F. (Chem. Soc. Rev., 2017)

(untitled) - Jurkauskas, V.; Sadighi, J. P.; Buchwald, S. L. (Org. Lett., 2003)

(untitled) - Harada, A.; Makida, Y.; Sato, T.; Ohmiya, H.; Sawamura, M. (J. Am. Chem. Soc., 2014)

(untitled) - Ohmiya, H.; Zhang, H.; Shibata, S.; Harada, A.; Sawamura, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Yasuda, Y.; Ohmiya, H.; Sawamura, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hojoh, K.; Ohmiya, H.; Sawamura, M. (J. Am. Chem. Soc., 2017)

(untitled) - Yasuda, Y.; Ohmiya, H.; Sawamura, M. (Synthesis, 2018)

(untitled) - Clavier, H.; Coutable, L.; Guillemin, J.-C.; Mauduit, M. (Tetrahedron: Asymmetry, 2005)

(untitled) - Martin, D.; Kehrli, S.; d'Augustin, M.; Clavier, H.; Mauduit, M.; Alexakis, A. (J. Am. Chem. Soc., 2006)

(untitled) - Shintani, R.; Takatsu, K.; Takeda, M.; Hayashi, T. (Angew. Chem., Int. Ed., 2011)

(untitled) - Guo, S.; Zhou, J. (Org. Lett., 2016)